NEW ECONOMIC CONCEPTS SHAPING BUSINESS MODELS IN POST-PANDEMIC ERA (International Journal of Innovative Technologies in Economy, 2021)
Low-Touch Economy is emerging due to the COVID-19 pandemic that has caused dramatic changes in all aspects of society including the way business is operating. The lockdown policies aiming at avoiding the spread of the new coronavirus in almost every country led to disruptions in business continuity.The aim of this paper is to overview a new concept of Low-Touch Economy and its possible implications on Business Models in connection with the Digital Economy. The article also outlines the concept in light of the circular and sharing economic theories. The exploratory research approach allows reviewing the current literature and gathering secondary data about Low-Touch Economy and its implications on business dealings. The Bibliographic research of recent works shows the role of the Low-Touch Economy and Digital Economy in searching for new business models and their potential to accelerate economic recovery after the pandemic.The article concludes by suggesting that organizations should adapt their business models to the new reality. It contributes to a current ongoing discussion on ways out of the crisis. This article fulfills an identified need to study how Low-Touch Economy along with Digital Economy can help the business to continue operations during the pandemic and how the concepts underpinning business models can enable fast economic recovery. Future empirical research will reveal the capability of the Low Touch Economy in different industries as well as various countries around the globe.